ANALISIS KUALITAS LAYANAN PADA PERUSAHAAN JASA TAKSI CV. DHAFIN DI PONTIANAK (RUTE SAMBAS - PONTIANAK) - B11108104, Reni Suhada (Jurnal Manajemen Update, 2013)
The title of this research is analysis of the quality of service on a service companies a taxi CV.DHAFIN in Pontianak (route Sambas -Pontianak). This research explain how the quality of service company taxi CV. DHAFIN in Pontianak ( route Sambas - Pontianak ). The purpose of this research is determine the level of the services provided by service company taxi. CV. DHAFIN to the its consumers after using the service with (route Sambas - Pontianak). A method of research that we use is a method of surveying, namely by the technique of collecting data primary by means of interviews and the spread of a questionnaire, and collecting data secondary namely data is collected directly, not of its object but had mixed by other parties of the internet, like websites agencies related companies and other data that deals with the object research to furnish data is needed. The sample done with the methods purposive of sampling with a sample of as many as 100 people respondents it is never used a taxi services CV. DHAFIN(route Sambas - Pontianak ) in this context is the consumer service users taxi Dhafin (route Sambas - Pontianak). Engineering analysis of data used is statistics descriptive namely acquire a sense of what the condition of the quality of service, as well as to identify carateristic a carpel of - each variable service in the form of the frequency and percentace. Besides that also used diagrams cartesius that are a part divided over four parts bounded by two perpendicular lines that intersect at the point of X and Y where X to see value rerata the level of performance and Y to see value rerata from the level of interest. Based on the research that in general the quality of service on services company taxi CV.DHAFIN in Pontianak (route Sambas - Pontianak) is been both according to customers, perception but, some variable that still needs to be exclusively by the company, due to all indicators considered important by users taxi Dhafin but service perceived not satisfactory namely punctuality to fetch and ushered in passengers to the destination, ease in ticket selling taxi dhafin,a guarantee that goods (baggage) will to destination,employees dhafin, ability employees in dealing with complaints, employees being warm hearted and want believed that if something is wrong. Keyword : Service Quality